2021
DOI: 10.1002/saj2.20239
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochar, digestate, and process water impacts on a soil's microbial community, processes, and metal bioavailability

Abstract: Hydrothermal carbonization converts organic wastes into potentially soil-improving solids. The nutrient-rich process waters generated are prospective fertilizers. Two hydrochars were produced from maize (Zea mays L.) biogas digestate after 1 or 6 h of carbonization. Nutrient concentrations of the digestate, hydrochars, and process waters were determined. A 28-d incubation, in which digestate, hydrochars, or process waters were added to a sandy loam soil, assessed their effects on microbial biomass, community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…For instance, Adani, et al [41] observed a 50% increase in labile carbon loss as a result of a 75% increase in the compost dose. Nevertheless, the potential storage of freshly added C pools through digestate amendment strongly dependent on either the anaerobic biogas properties or the recipient soil characteristics [42][43][44][45]. We surmise that the pedogenetic features of the studied olive grove soil rich in fine-textured particles, poor in calcium carbonate, and with limited aeration produced soil fabric conditions suitable for physical protection and reduced mineralization of newly added organic pools, whatever their content of easily degradable organic substrates.…”
Section: Soil Chemical Propertiesmentioning
confidence: 83%
“…For instance, Adani, et al [41] observed a 50% increase in labile carbon loss as a result of a 75% increase in the compost dose. Nevertheless, the potential storage of freshly added C pools through digestate amendment strongly dependent on either the anaerobic biogas properties or the recipient soil characteristics [42][43][44][45]. We surmise that the pedogenetic features of the studied olive grove soil rich in fine-textured particles, poor in calcium carbonate, and with limited aeration produced soil fabric conditions suitable for physical protection and reduced mineralization of newly added organic pools, whatever their content of easily degradable organic substrates.…”
Section: Soil Chemical Propertiesmentioning
confidence: 83%
“…Compared to pyrolysis, the temperature of hydrothermal carbonization is relatively lower than that of pyrolysis, and the yield of coke obtained is also higher than that of pyrolysis (the carbon yield of hydrothermal carbonization reaches 20-80%). It is a promising alternative thermal conversion technology [74]. During hydrothermal carbonization, wet organic raw materials are generated into liquid, solid, and gas phases at a temperature of 180-250 • C and a self-pressure of 2-10 Mpa.…”
Section: Preparation Of Porous Carbon Materialsmentioning
confidence: 99%
“…32 The soils were incubated for 28 days, in line with other soil and OW incubation studies focused on heavy metals issues. 30,[33][34][35] Nano- 68 ZnS was added to soil according to actual fertilizing practice (OW spreading rate: 0.01 kgOW.kgsoil -1 ) and considering OW with 1000 mg.kgOW -1 of Zn as nano-ZnS. A corresponding amount of nano-68 ZnS (10 mgZn.kgDM soil -1 ) was mixed with dried soil (40°C) using a powder mixer (Turbula ® T2F T10B).…”
Section: Incubation Experiments For In Situ Monitoring Of Zn Availabi...mentioning
confidence: 99%